Impacts of agricultural machine renting on cereal crop productivity and commercialization in West Gojjam Zone, Ethiopia - Selam Tilahun; Berhanu Kuma; Amsalu Bedemo (PLoS ONE, 2025)
Agricultural mechanization plays an essential role to increase production, productivity and commercialization of cereal crops. Despite the Ethiopian’s government has made substantial efforts to increase production, productivity and commercialization of cereal crops by the introduction of selective and adaptable agricultural machines to smallholder farmers has remained low. This study, therefore, investigated the impacts of agricultural machine renting on cereal crop productivity and commercialization. The study used cross-sectional data collected from 192 agricultural machine users and 208 non-users from West Gojjam zone, Ethiopia. The data were analyzed using descriptive statistics and econometric models. The econometric model includes Trans log production function, Endogenous switch regression and propensity score matching. The result of descriptive statistics showed that the total factor productivity index of the cereal crop was 2.89, and the mean commercialization index for the sample households was 0.506. The estimation of results of Trans log production function model showed an average level of Technical Efficiency of 80.6%. The result of first stage Endogenous switch regression model showed that age, education level, ownership of oxen, total cultivated land, extension visit, access to information, family size, the position a farmer, and distance to the nearest market significantly affected adoption of agricultural machine renting. The result of endogenous switching regression and propensity score matching models showed that agricultural machine renting had a positive and significant impact on the selected outcome variables, total factor productivity, technical efficiency and output commercialization index. Based on the findings, the study suggests that the government and stakeholders should focus on strengthening the provision of education, development of infrastructures, extension service, to promote agricultural machine renting service, and enhance cereal crops productivity and commercialization.